Self-Efficacy and Qur’anic Tahsin Learning in School-Based Islamic Education: (Efikasi Diri dan Pembelajaran Tahsin Al-Qur’an dalam Pendidikan Islam Berbasis Sekolah) - Zennanta Agustia; Retno Widyaningrum (Journal of Islamic Education and Intellectual Discourse (JIED), 2026)
Qur’anic tahsin learning requires accurate articulation, consistent tajwid application, reading fluency, and students’ readiness to receive corrective feedback. This study examined the effect of self-efficacy on students’ Qur’anic tahsin ability in Ponorogo, a regency where religious-based education in basic education is formally supported by Peraturan Bupati Ponorogo No. 37 of 2022. A quantitative associative design was applied to 216 junior secondary students. Self-efficacy was measured using a 20-item Likert questionnaire, while tahsin ability was obtained from school-documented tahsin assessment scores. Data were analyzed using IBM SPSS through validity testing, reliability testing, descriptive statistics, residual diagnostics, linearity testing, and simple linear regression. The self-efficacy instrument was valid, with item-total correlations ranging from .593 to .712, and reliable, with Cronbach’s alpha of .931. The regression model was statistically significant, F(1, 214) = 83.817, p < .001. Self-efficacy positively predicted Qur’anic tahsin ability, B = .258, SE = .028, β = .531, t = 9.155, p < .001. The model explained 28.1% of the variance in tahsin ability. These findings indicate that self-efficacy is a meaningful psychological factor in tahsin learning and should be considered in school-based Qur’anic education programs.